L' éducation communiste : discours et articles choisis - Kalinine, Michail Ivanovitch (Moscou : Editions en Langues Etrangères, 1951)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: opvoeding; Sovjet-Unie.